2010
DOI: 10.1007/s00775-010-0727-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of sulfonate ester based matrix metalloproteinase proinhibitors by hydrogen peroxide

Abstract: This study details the development of matrix metalloproteinase inhibitor prodrugs (proMMPi) that are activated in the presence of reactive-oxygen species (ROS). Conventional matrix metalloproteinase inhibitors (MMPi) utilize a zinc-binding group (ZBG) that chelates to the catalytic zinc(II) ion of matrix metalloproteinases (MMPs) to inhibit their activity. To create ROS-sensitive prodrugs, sulfonate esters were used as a protecting group for the ZBG to block their metal binding ability. Surprisingly, these sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…[39][40][41][42][43][44] The presence of increased concentrations of H2O2 in the inflammatory environment can serve as the stimulus for prodrug activation in site-selective drug delivery systems. Phenylboronic acids and esters, [45][46][47][48] phenylsulfonate esters, 49 thiazolidinones, 44 N- (2,5-dihydroxyphenyl)acetamides, 50 and α-boryl ethers, carbonates, and acetals 51 have been reported as useful structural motifs for hydrogen peroxide activatable prodrugs and imaging, but studies have mainly focused on their applications in oncology.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42][43][44] The presence of increased concentrations of H2O2 in the inflammatory environment can serve as the stimulus for prodrug activation in site-selective drug delivery systems. Phenylboronic acids and esters, [45][46][47][48] phenylsulfonate esters, 49 thiazolidinones, 44 N- (2,5-dihydroxyphenyl)acetamides, 50 and α-boryl ethers, carbonates, and acetals 51 have been reported as useful structural motifs for hydrogen peroxide activatable prodrugs and imaging, but studies have mainly focused on their applications in oncology.…”
Section: Introductionmentioning
confidence: 99%
“…Hence compounds 15a–b were not stable and even in the absence of ROS, the sulfonate ester groups would dissociate to produce 1,2-HOPO-2. 59 Due to this and other limitations, we turned our efforts to other ROS-sensitive protecting groups, in order to establish a better performing prodrug platform.…”
Section: Exploiting the Metal-ligand Interaction: A Case For Metallopmentioning
confidence: 99%
“…Structure of ROS-activated MMP inhibitor prodrugs based on sulfonate ester (top) 59 and boronate ester self-immolative (bottom) 60 protecting groups.…”
Section: Figmentioning
confidence: 99%
“…Given the significantly high H 2 O 2 concentrations (5–1000 μM) in cancer cells relative to normal cells (0.001–0.7 μM), Peng et al ,18 for the first time, reported boron-based nitrogen mustard precursors as selective anticancer agents in 2011, followed by the blooming of various prodrugs (over 50 published papers) bearing an arylboronic acid/ester as the H 2 O 2 -cleavable trigger between 2012–2019 (Table S1†). Other H 2 O 2 -responsive moieties, such as arylsulfonyl ester,19 thiazolidinone,20 and benzothiazole21 have also been reported for constructing small molecule prodrugs, but with very limited examples of each. In addition, sulfide, thioether, thioketal, selenium, and peroxalate ester are also known as H 2 O 2 -sensitive scaffolds, but in most cases, their applications are confined to polymers or nanoparticles 22,23.…”
Section: Introductionmentioning
confidence: 99%